Correlation of Cardiac Sympathetic Nervous System Dysfunction with Diastolic Left Ventricular Dysfunction in Patients with Controlled Hypertension - Elsayed Abo-salem; Mouhamad Abdallah; Mohamed Effat; Said Alsidawi; Myron Gerson (Archives of Clinical Hypertension - Peertechz Publications, 2016)
Introduction: Sympathetic nervous system activity is increased in patients with systemic hypertension. Angiotensin converting enzyme inhibitors can effectively control hypertension without a reflex sympathetic stimulation. However, limited data are available about the role of sympathetic dysfunction in the   pathophysiology of diastolic dysfunction among patients with controlled hypertension receiving angiotensin converting enzyme inhibitors. Methods: Twenty four non-diabetic patients with controlled hypertension on angiotensin converting enzyme inhibitors without heart failure and not currently on β-blocker therapy were included in the study. Patients were divided into 2 groups based on diastolic function as defined by echocardiography, group A with diastolic dysfunction (10 subjects) and group B without diastolic dysfunction (14 subjects). Patients underwent ambulatory blood pressure monitoring for assessment of nocturnal blood pressure dip and 123I metaiodobenzylguanidine (123I-MIBG) imaging to determine heart to mediastinum ratio. Plasma norepinephrine levels were measured. Result: Patients with diastolic dysfunction had a higher level of plasma norepinephrine (0.46 vs 0.26 ng/ml, p=0.01) as compared to patients with normal diastolic function. There was no statistically significant difference in the early or late heart to mediastinum ratio (p=0.5) or the wash-out rate (p=0.9) among the two groups. There was no correlation between plasma norepinephrine and 123I-MIBG uptake. There was a statistically significant inverse correlation between E/A ratio and the log of plasma norepinephrine level (r= - 0.43, P=0.03). Conclusion: Localized cardiac autonomic dysfunction is not significantly worse in grade I diastolic dysfunction, compared to normal